Childhood Effects of Prenatal and Postnatal Exposure to Mercurial Skin Lightening Agents. Literature Review - Rebecca Murerwa; Fidel Gwala; Thomas Amuti; Mary Muange (University Library System, University of Pittsburgh, 2022)
Children's exposure to mercurial skin lightening agents at any time during their development, from intra-uterine to early developmental life, can lead to severe detrimental health effects. This is because these skin lightening agents contain inorganic mercury as their active ingredient at varying concentrations that exceed acceptable levels. Mercury does not confer any physiological benefit to the human body, and as such, it has only been linked to numerous adverse effects on users and may pose a possible health risk for children born to, living with, and in contact with skin bleaching agent users. Although studies have shown that inorganic mercury exposure may be detrimental to children, there is a paucity of data, to the best of our knowledge, on reviews exploring specifically the possible routes of exposure to and effects of mercurial skin lightening agents on children. Since prevention is the only key to reducing mercury poisoning and toxicity, this study aims to extensively review the literature on prenatal and postnatal exposure to mercury in children from cosmetic skin lightening agents and discuss possible detrimental effects.